Elements of lake macrophyte metacommunity structure: Global variation and community‐environment relationships. (30th July 2020) - García‐Girón, Jorge; Heino, Jani; Baastrup‐Spohr, Lars; Clayton, John; de Winton, Mary; Feldmann, Tõnu; Fernández‐Aláez, Camino; Ecke, Frauke; Hoyer, Mark V.; Kolada, Agnieszka; Kosten, Sarian; Lukács, Balázs A.; et al.
Abstract: Documenting the patterns of biological diversity on Earth has always been a central challenge in macroecology and biogeography. However, we are only beginning to generate an understanding of the global patterns and determinants of macrophyte diversity. Here, we studied large‐scale variation and community‐environment relationships of lake macrophytes along climatic and geographical gradients using regional data from six continents. We applied statistical routines typically used in the context of metacommunity studies to provide novel insights into macrophyte community compositional patterns within regions worldwide. We found that lake macrophyte metacommunities followed clumped species replacement structures, suggesting that two or more species groups were responding similarly to the environment within regions. Underlying such general convergence, our results also provided evidence that community‐environment relationships were largely context‐dependent, stressing that no single mechanism is enough to account for the complex nature of compositional variation. Surprisingly, we found no general relationships between functional or phylogenetic composition and main metacommunity types, suggesting that linking multi‐trait and evolutionary information to the elements of metacommunity structure is not straightforward. Our findings highlight that global conservation initiatives and biodiversity protection need to capture environmental variation at the metacommunity level, and acknowledge the highly context‐dependent patterns in the community‐environment relationships of lake macrophytes. Overall, we emphasize the need to embrace the potential complexity of ecological inferences in metacommunity organization across the globe.